Investigating Sources of Heterogeneity in Randomized Controlled Trials of the Effects of Pharmacist Interventions on Glycemic Control in Type 2 Diabetic Patients: A Systematic Review and Meta-Analysis. - Patricia Melo Aguiar; Giselle de Carvalho Brito; Tácio de Mendonça Lima; Ana Patrícia Alves Lima Santos; Divaldo Pereira Lyra; Sílvia Storpirtis (PLoS ONE, 2016)
Objective To assess the effect of pharmacist interventions on glycemic control in type 2 diabetic patients and to examine factors that could explain the variation across studies. Methods A comprehensive literature search was performed in PubMed, Scopus, and LILACS databases for randomized controlled trials (RCTs) published up to July 2015. The search strategy included the use of MeSH terms or text words related to pharmacist interventions, type 2 diabetes, and randomized controlled trials. RCTs published in English, Portuguese, or Spanish that evaluated the effect of pharmacist intervention on glycemic control in type 2 diabetic outpatients were included. Two independent authors executed study selection, data extraction, and risk of bias assessment. Mean differences in glycosylated hemoglobin (HbA1c) were estimated using random-effect models, and heterogeneity was evaluated by subgroup and meta-regression analyses. Results The literature search yielded 963 records of potential interest, of which 30 were included in the systematic review and 22 in the meta-analysis. Most of these RCTs were conducted in the United States in patients in outpatient clinics using face-to-face contact only. All RCTs performed patient education, and most executed the medication review. The appraised sample showed uncertain or high risk of bias in most of the items evaluated, resulting in low-quality studies. In comparison with usual care, pharmacist interventions were associated with significant reductions in HbA1c levels (-8.5% [95% CI: -1.06, -0.65]; P < 0.0001; I2 = 67.3%). Subgroup analysis indicated differences of heterogeneity by country, baseline HbA1c levels, setting, intervention frequency, and random allocation. Age and HbA1c levels partly explained the variability across studies by meta-regression. Conclusions Our findings confirmed that pharmacist interventions improve glycemic control in patients with type 2 diabetes compared with usual care and suggest that younger patients or with higher baseline HbA1c levels may be the main beneficiaries of pharmacist care. Protocol prospero registration number CRD42014007457.